Measurement of the Minimal Diameter of Non-Metastatic Jugulodigastric Lymph Nodes Using Ultrasonography - ATSURA, Kouji; KOHNO, Masaki; HINOKI, Ayumi; TAIRA, Shuhzou; HAYASHI, Takafumi; ITO, Jusuke (Shika Hoshasen, 2000)
The purpose of this study was to investigate the age distribution of the minimal diameter of non-metastatic jugulodigastric lymph nodes seen on ultrasonography to establish a reliable criterion to differentiate metastatic from non-metastatic lymph nodes. Between October 1998 and November 1999, 386 patients with obstructive sleep apnea syndrome were examined using neck ultrasonography to evaluate atherosclerosis of the common carotid artery and the minimal diameter of jugulodigastric lymph nodes were measured simultaneously. The study cohort consisted of 100 Japanese males extracted at random ranging in age from 31 years to 79 years (average: 54.3 years). Patients with any oral malignancies were excluded. The minimal diameter of the node was 8.8 mm on average in patients in the fourth decade, 8.1 mm in the fifth decade, 7.2 mm in the sixth decade, 7.0 mm in the seventh decade, 7.0 mm in the eighth decade, respectively. A significant difference was observed between the fourth decade and the sixth decade or older using post hoc test (p<0.05): If the cut-off point of the minimal diameter should be 8 mm, the specificity was 45% in patients in the fourth decade, 70% in the fifth decade, 85% in the sixth decade, 85% in the seventh decade, 85% in the eighth decade, respectively. In conclusion, the minimal diameter of 8 or 9 mm in the jugulodigastric lymph nodes, which is the currently accepted criterion for metastatic lymph nodes on ultrasonography, might be almost adequate as the cut-off point. Additionally, we recommend that the cut-off point should be lmm larger in patients in the fourth decade than in patients in the sixth decade or older.